2020
DOI: 10.26434/chemrxiv.12468170.v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Linking Void and Interphase Evolution to Electrochemistry in Solid-State Batteries Using Operando X-Ray Tomography

Abstract: <p>Despite progress in solid-state battery engineering, our understanding of the chemo-mechanical phenomena that govern electrochemical behavior and stability at solid-solid interfaces remains limited compared to solid-liquid interfaces. Here, we use <i>operando</i> synchrotron X-ray computed microtomography to investigate the evolution of lithium/solid-state electrolyte interfaces during battery cycling, revealing how the complex interplay between void formation, interphase growth, and volum… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 0 publications
0
25
0
Order By: Relevance
“…Recent studies have also demonstrated that stripping at Li/SSE interfaces plays a major role in destabilizing subsequent lithium deposition [25][26][27][28][29] . Stripping current densities that exceed the rate at which lithium can be replenished at the interface via deformation and/or self-diffusion lead to contact loss through the formation of interfacial voids.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have also demonstrated that stripping at Li/SSE interfaces plays a major role in destabilizing subsequent lithium deposition [25][26][27][28][29] . Stripping current densities that exceed the rate at which lithium can be replenished at the interface via deformation and/or self-diffusion lead to contact loss through the formation of interfacial voids.…”
Section: Introductionmentioning
confidence: 99%
“…Stripping current densities that exceed the rate at which lithium can be replenished at the interface via deformation and/or self-diffusion lead to contact loss through the formation of interfacial voids. Contact loss causes higher current densities at the interface, and current constriction at the edges of interfacial voids further increases local current densities 10,25 . When plating occurs after contact loss, these higher local current densities increase the likelihood that lithium will penetrate through the SSE to form a short circuit.…”
Section: Introductionmentioning
confidence: 99%
“…14 Notably, progress in the field of X-ray imaging allowed for the elucidation of solid-state batteries while under operation. [15][16][17][18] However, the identification of lithium is challenging.…”
Section: Mainmentioning
confidence: 99%
“…However, intrinsic thermodynamic, electrochemical and mechanical instability between the components of the SSB significantly limits their performance 4 . These unfavorable electro-chemo-mechanical behavior at the numerous solid | solid interfaces within the SSB leads to non-optimal material utilization, mechanical degradation, and poor ion transport 1,5,6,7,8,9,10,11 . These phenomena transcend several orders of magnitude in timeand length-scales and are yet to be fully understood.…”
Section: Introductionmentioning
confidence: 99%